Pola Perdagangan Internasional dalam Era Globalisasi Sebuah Kajian Deskriptif - Muhammad Dwi Arif (Jurnal Pendidikan Manajemen Transportasi, 2024)
This study aims to determine and explain the patterns, trends, and factors that influence international trade in the era of globalization. In this study, the author uses a descriptive method by collecting data from various sources and then analyzing it to identify patterns, trends, and factors that influence international trade. The results show that the growth of global trade has been driven by a number of factors, such as: (1) Reduction of trade barriers; (2) The emergence of free trade agreements (3) The growth of multinational companies; (4) The development of new technologies. The value of global trade has also increased dramatically over the past three decades, from $12.5 trillion in 1990 to $25.6 trillion in 2019. This shows that international trade has emerged as an important component of the world economy. From the results of the research and discussion carried out, it can be concluded that global trade has grown rapidly in recent decades, driven by various factors.